Gauged N = 2 Supergravity from Type II Compactiﬁed on Calabi-Yau 3-Fold with Background Fluxes - Bobby E. Gunara; Freddy P. Zen; Arianto Arianto (Indonesian Journal of Physics, 2004)
We address some geometrical aspects of a special class of four dimensional N = 2 supergravity theory obtained from Calabi-Yau compactiﬁcation of the Type II supergravities with background Ramond-Ramond (RR) ﬂuxes.In particular, several properties of the vector multiplet and hypermultiplet scalar manifolds determined by Calabi-Yau geometry and its deformation are considered. Moreover, aspects of background magnetic and electric ﬂuxes on Calabi-Yau 3-fold which imply that the scalar manifolds have to be gauged with respect to their isometries related to the ﬂuxes. We ﬁnally investigate the arising scalar potential and their vacua.